2019
DOI: 10.3329/jbau.v17i4.44604
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Trichoderma species against important fungal pathogens causing post-harvest rot in sweet potato (Ipomoea batatas (L.) Lam)

Abstract: Tuber rot disease constitutes a serious threat to sweetpotato production worldwide, causing economic losses to farmers.  This study evaluated an eco-friendly approach using four biological control agents, Trichoderma viride, T. harzianum, T. hamatum and T. pseudokoningii for the management of post-harvest tuber rot disease of sweetpotato. Field surveys for infected tuber samples were conducted four across major sweetpotato states in Nigeria. Rot severity in inoculated tubers was evaluated over a storage period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Through the use of natural enemies like microbes in the ecosystem, biological control is an effective and environmentally friendly way to lower the prevalence of disease (Dania, 2019). The goal of biological control agents (BCAs) is to significantly lower the prevalence of disease while also enhancing the ability of hormones that promote growth to promote plant development and ultimately yield (Pascal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the use of natural enemies like microbes in the ecosystem, biological control is an effective and environmentally friendly way to lower the prevalence of disease (Dania, 2019). The goal of biological control agents (BCAs) is to significantly lower the prevalence of disease while also enhancing the ability of hormones that promote growth to promote plant development and ultimately yield (Pascal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma species T. reesei, T. virens, and T. atroviride have their genomes examined, and the results indicated that mycoparasitism is an intrinsic trait of Trichoderma; yet, these species also exhibit significant nutritional versatility: Trichoderma species have an exceptional propensity to create enzymes that cause lysis of the host cell, which promoted their use as a biocontrol agent against plant pathogenic fungus in addition to acting as mycoparasite (Kubicek et al, 2019). According to Dania (2019), Trichoderma species exhibit an exceptional propensity to create enzymes that lyse the target pathogens' mycelia and result in the formation of secondary metabolites or antibiotics. With more than 1500 registered preparations worldwide (Verma et al, 2007), they are the most common natural fungicides used in commercial farming (Dania, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These beneficial fungi are competitors in the soil environment to pathogen species and synthesize secondary metabolites to decrease plant pathogens [21] by an interference competition [22]. Moreover, Trichoderma fungi can produce peroxidases, glucanases, chitinases, and cellulases, enzymes active against phytopathogens [23,24] used in the postharvest disease management of papaya, apple, tomato, pear, mango, banana, potato, and berries [25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%